Association between serum and oral matrix metalloproteinase‐8 levels and periodontal health status. (27th March 2017) - Noack, B.; Kipping, T.; Tervahartiala, T.; Sorsa, T.; Hoffmann, T.; Lorenz, K.
Abstract : Background and Objective: Matrix metalloproteinase‐8 (MMP‐8) is involved in a wide range of pathologies including periodontitis and cardiovascular diseases (CVD). The association between periodontitis and CVD has been repeatedly recognized. The aim of the study was to analyze to what extent circulating active MMP‐8 (aMMP‐8) is associated with periodontal disease status and oral fluid aMMP‐8 levels in otherwise healthy subjects. Material and Methods: In a cross‐sectional study, aMMP‐8 was measured in serum of 59 volunteers, comprising 19 periodontally healthy subjects, 20 patients with gingivitis as well as 20 with periodontitis. All study subjects were characterized regarding aMMP‐8 concentrations in different oral fluids as well as clinically and microbiologically with respect to periodontal disease. aMMP‐8 levels in gingival crevicular fluid were measured using the enzyme‐linked immunosorbent assay. Saliva enzyme levels as well as circulating aMMP‐8 were determined by a time‐resolved immunofluorometric assay. Both methods utilized the same monoclonal antibodies. Correlation and regression analyses were performed to study the potential association between serum aMMP‐8 and oral parameters. Results: Oral aMMP‐8 levels were significantly higher in patients with periodontitis compared to periodontally healthy or gingivitis subjects. Highest serum aMMP‐8 concentration was also found in the periodontitis group. The serum levels correlated significantly with oral aMMP‐8 as well as with clinical parameters in a dose‐dependent manner. These results were confirmed in a multivariate regression analysis. After adjusting for potential confounders, saliva aMMP‐8 concentrations as well as periodontitis severity were significant predictors of serum aMMP‐8. Conclusion: The associations between circulating aMMP‐8 and oral aMMP‐8 as well as periodontal findings in a dose‐dependent manner may contribute to linking periodontal disease with increased CVDsusceptibility.